Exploring the effect of digital and multisensory educational materials on retention in primary school using Tangible User Interfaces - Di Fuccio, Raffaele; Ponticorvo, Michela; Nadim, Muhammad Amin; Limone, Pierpaolo (Interactive learning environments, 2025)
The spreading of digital tools for learning has been impressive in later years. Some attempts have been made to augment traditional tools with digital solutions, still offering the chance to propose multisensory stimulation and interactivity. In this context, the aim of this study is to strengthen the importance of a multisensorial approach as a key factor in the development of learning devices in educational settings. We focused on investigating if there was a significant difference in knowledge retention when adding to the learning experience the stimulation of increasingly more sensorial channels using tangible interfaces. Results indicate that children recall more information if the interface is enhanced through multisensory materials including auditory, visual, and olfactory stimuli. This effect is even stronger when the time between exposition and recall is longer. This study supports the potential of merging digital and physical elements in educational materials to foster learning, in particular, it adds new data supporting the use of the sense of smell to improve memory retention.